THE ORIGINS OF THE FOURTH INTERNATIONAL IN ARGENTINA. LIBORIO JUSTO AND THE CASE OF GRUPO OBRERO REVOLUCIONARIO AND LIGA OBRERA REVOLUCIONARIA - Bosch Alessio, Constanza Daniela (2016)
This paper aims to reconstruct the political praxis of two Trotskyist groups in the late thirties in Argentina: the Grupo Obrero Revolucionario and its successor the Liga Obrera Revolucionaria. Both of them were led by Liborio Justo, son of former Argentine president Agustin Justo. The experience of GOR-LOR was relevant because of the variety and circulation of its publications and its political links with similar groups in Argentine and Latin American countries such as Cuba, Chile, Bolivia, Uruguay and Brazil.